THE BENEFITS ON AUTHENTIC ASSESSMENT APPLICATION IN TECHNIQUE AND MANAGEMENT OF LABORATORY LECTURE IN BIOLOGY EDUCATION DEPARTMENT FKIP OF RIAU UNIVERSITY - Yuslim Fauziah '; Yustini Yusuf '; Nurhidayati ' ' (Program Studi Pendidikan Biologi, 2015)
This research aims to get the description of students' perceptions about the benefits of authentic assessment application in Technique and Management of laboratory (TML) lecture in Biology Education Department FKIP of Riau University Academic Year 2013/2014. Subjects were 54 students of the 1st semester of Biology Education, Academic Year 2013/2014 consisting of 7 men and 47 women. The measured parameters were perceptions of students to benefit in the aspect of knowledge, reasoning, skills, work (Product), and attitude (Affect). The results showed that student had good perceptions about authentict assessment aplication and get the benefits in the aspect of knowledge with score 3.44 (good category), reasoning score 3.24 (good category), skill score 3.47 (good category), product is 3.25 (good category) and attitude aspect score 3.28 (good category). Aplication of authentict assessment has good benefits on Technique and Management of Laboratory lecture in Biology Education Department, FKIP Riau University.Keywords: Authentic Assessment, Technique And Management Of Laboratory